2009
DOI: 10.1073/pnas.0910243107
|View full text |Cite
|
Sign up to set email alerts
|

Label-free detection of protein-protein interactions using a calmodulin-modified nanowire transistor

Abstract: In this study, we describe a highly sensitive and reusable silicon nanowire field-effect transistor for the detection of protein-protein interactions. This reusable device was made possible by the reversible association of glutathione S-transferase-tagged calmodulin with a glutathione modified transistor. The calmodulin-modified transistor exhibited selective electrical responses to Ca 2þ (≥1 μM) and purified cardiac troponin I (∼7 nM); the change in conductivity displayed a linear dependence on the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
66
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(69 citation statements)
references
References 29 publications
0
66
0
3
Order By: Relevance
“…As shown in Table 1, several studies have used NWFET-based biosensors for label-free, ultra-high-sensitivity, and real-time detection of various biological targets, including a single virus 2 , adenosine triphosphate and kinase binding 3 , neuronal signals 4 , metal ions 5,6 , bacterial toxins 7 , dopamine 8 , DNA [9][10][11] , RNA 12,13 , enzyme and cancer biomarkers [14][15][16][17][18][19] , human hormones 20 , and cytokines 21,22 . These studies have demonstrated that NWFET-based biosensors represent a powerful detection platform for a broad range of biological and chemical species in a solution.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, several studies have used NWFET-based biosensors for label-free, ultra-high-sensitivity, and real-time detection of various biological targets, including a single virus 2 , adenosine triphosphate and kinase binding 3 , neuronal signals 4 , metal ions 5,6 , bacterial toxins 7 , dopamine 8 , DNA [9][10][11] , RNA 12,13 , enzyme and cancer biomarkers [14][15][16][17][18][19] , human hormones 20 , and cytokines 21,22 . These studies have demonstrated that NWFET-based biosensors represent a powerful detection platform for a broad range of biological and chemical species in a solution.…”
Section: Introductionmentioning
confidence: 99%
“…1). The reusable device is made possible by the reversible association of glutathione S-transferase-tagged CaM with a glutathione-modified transistor (Lin et al, 2010). The minimum concentration of Ca 2+ required to activate CaM is 1 mM, and this sensitive nanowire transistor can serve as a high-throughput biosensor and substitute for immunoprecipitation methods used in the identification of interacting proteins.…”
mentioning
confidence: 99%
“…These target proteins are involved in almost all aspects of plant growth and development as well as in responses to abiotic and biotic stresses. Recently, an mRNA display technique and a CaM-modified nanowire transistor method have been developed for isolating CaM-binding proteins in humans (Shen et al, 2005;Lin et al, 2010). The mRNA display technique to identify Ca 2+ /CaM-binding proteins is to screen the mRNA-displayed proteome libraries with biotinylated CaM.…”
mentioning
confidence: 99%
“…In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1, 2), single-walled carbon nanotubes (1, 3, 4), and graphene (1, 5, 6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7). Subsequent studies have demonstrated highly sensitive and in some cases multiplexed detection of key analytes, including protein disease markers (8-10), nucleic acids (11-13), and viruses (14), as well as detection of protein-protein interactions (8,(15)(16)(17) and enzymatic activity (8).The success achieved with nanomaterial-based FET biosensors has been limited primarily to measurements in relatively low-ionicstrength nonphysiological solutions due to the Debye screening length (18,19). In short, the screening length in physiological solutions, <1 nm, reduces the field produced by charged macromolecules at the FET surface and thus makes real-time label-free detection difficult.…”
mentioning
confidence: 99%
“…In particular, field-effect transistor (FET) biosensors configured from semiconducting nanowires (1, 2), single-walled carbon nanotubes (1, 3, 4), and graphene (1, 5, 6) have been extensively investigated since the first report of real-time protein detection using silicon nanowire devices (7). Subsequent studies have demonstrated highly sensitive and in some cases multiplexed detection of key analytes, including protein disease markers (8-10), nucleic acids (11-13), and viruses (14), as well as detection of protein-protein interactions (8,(15)(16)(17) and enzymatic activity (8).…”
mentioning
confidence: 99%